Early recognition of pain: improving colic outcomes in horses in Senegal - Laleye, B. O. F-X. V.; Seye, Mamadou; Chiavaccini, Ludovica (Frontiers in Pain Research, 2024)
BackgroundLimited knowledge exists on recognition and treatment of equine abdominal pain in low- and middle-income countries. This study aimed at finding indicators for recognizing abdominal pain, evaluating responses to clinical and behavioral changes, and assessing the impact of timely referral on colic outcomes in a suburban region of Senegal. The final goal was to identify factors that may be leveraged to improve the outcome of horses presented for abdominal pain in Senegal.Study designRetrospective, observational cohort study.MethodsData from 26 foals and 40 adult horses referred for acute abdomen between 2013 and 2014 and the first semester of 2023 were reviewed. Signs of abdominal pain were grouped into behavioral, posture modification and animal interactions with the environment. Time to referral was defined as the time between the recognition of abdominal pain and referral. The association of time to referral and the outcome was calculated for each subpopulation and compared using logistic regression analysis as appropriate.ResultsA significant proportion of owners (47%) and veterinarians (77.8%) relied on behavioral changes to detect abdominal pain in foals. Most owners referred foals within 24 h, while veterinarians referred within 12 h. Mortality in foals exceeded 50% when referral was delayed by 12 h or more. In adult horses, groomers often were the first noticing behavioral changes (79%), and they referred the horse within three hours, whereas owners typically delayed referral for 24 h or longer, leading to increased hospitalization expenses.LimitationsThe study considered a limited cohort in an suburban area of Senegal. Sourcing complete data was challenging. Additionally, accurately assessing owner experience was difficult due to the participant group's heterogeneity. Absence of a reliable system to measure daily horse-owner interaction time and logistical challenges in the abdominal pain symptom alert chain were also limiting factors.ConclusionsEarly detection is critical for positive colic outcomes in both foals and adult horses. Therefore, raising awareness and providing training to horse owners for prompt recognition of symptoms and referral is essential. This proactive approach aims to improve overall outcomes and reduce the financial burden of equine hospitalization in Senegal.